Discussion on "An effective method for the explicit solution of sequential problems on the real line" by Sören Christensen. Issue 1 (2nd January 2017) - Tartakovsky, Alexander G.
ABSTRACT: Optimal stopping theory is a key part of sequential analysis and applied probability. Dr. Sören Christensen's article is an important contribution to solving a class of optimal stopping problems for Markov processes mainly in continuous time, but a certain expansion to discrete time is also given. This discussion contains several issues that naturally arise in many statistical applications.